Social and solidarity economy in higher education: a space for innovation (2020)
This first volume of the collection Social and Solidarity Economy in Higher Education: a space for innovation is made up of articles that account for the powerful link that is generated by introducing the reality, theory, and practice of the social and solidarity economy in the curriculum of universities in the United Kingdom, Colombia, Argentina, Canada, France, Spain, and Brazil. The authors present experiences that contribute to the improvement of institutional pedagogical models, to the development of competences for teachers and to the empowerment of young people from the classroom to influence their local realities. This is done through examples of curricular developments that lead to the management of cooperatives and the promotion of public policies in alliance with national governments. Also, experiences of dialogue of knowledge are exposed and it is shown how the link with agroecological markets can be a scenario of social appropriation of knowledge that stimulates citizen participation. In the last chapters, the importance of university ecosystems supporting the social and solidarity economy and the experience of incubators to tune the academic community with the territory are highlighted. Thus, how this strategy allows proposing effective solutions to social, economic and environmental problems or needs is highlighted through solidarity entrepreneurship and social innovation. As in the other volumes, it is evident that the experience of education in social and solidarity economy can not only respond to the demands of a changing world, it can also inspire the appropriation of the future for the achievement of the global common good.